2009
DOI: 10.1128/jvi.00231-09
|View full text |Cite
|
Sign up to set email alerts
|

Type I and Type II Interferons Inhibit the Translation of Murine Norovirus Proteins

Abstract: Human noroviruses are responsible for more than 95% of nonbacterial epidemic gastroenteritis worldwide. Both onset and resolution of disease symptoms are rapid, suggesting that components of the innate immune response are critical in norovirus control. While the study of the human noroviruses has been hampered by the lack of small animal and tissue culture systems, our recent discovery of a murine norovirus (MNV) and its in vitro propagation have allowed us to begin addressing norovirus replication strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 55 publications
4
89
0
Order By: Relevance
“…Overall, our data suggest that type I IFN can induce a PKR-independent pathway to block VACV protein translation and that this pathway can be inhibited by K1L and C7L. Interestingly, some recent studies with norovirus and picornavirus also suggest that a PKR-independent pathway is induced by type I IFN to inhibit protein translation in cells infected by these RNA viruses (8,20). Identification of the target for K1L and C7L may lead to the identification of a novel antiviral host factor/pathway that has broad antiviral effects.…”
Section: C7lmentioning
confidence: 75%
“…Overall, our data suggest that type I IFN can induce a PKR-independent pathway to block VACV protein translation and that this pathway can be inhibited by K1L and C7L. Interestingly, some recent studies with norovirus and picornavirus also suggest that a PKR-independent pathway is induced by type I IFN to inhibit protein translation in cells infected by these RNA viruses (8,20). Identification of the target for K1L and C7L may lead to the identification of a novel antiviral host factor/pathway that has broad antiviral effects.…”
Section: C7lmentioning
confidence: 75%
“…The discovery of MNV, along with its capacity to grow in a smallanimal model, provides an opportunity to investigate NoV pathogenesis in vivo in greater detail. Previous studies have used the MNV model to identify and characterize viral and host determinants of MNV infection (3,10,13,18,31,38,42,58,63). Some of these studies reveal a profound role for STAT1-dependent host responses as a major determinant of MNV replication and dissemination in vivo, as well as pathology and mortality following MNV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that IFN responses were critical to control MNV infection in vivo and inhibited viral replication in vitro (Karst et al, 2003;Wobus et al, 2004). Both type I and type II IFNs block the translation of viral proteins of MNV but while type II IFN-mediated inhibition is dependent on the well-characterized interferon-induced antiviral molecule PKR, type I IFNmediated inhibition occur through a PKR-independent process (Changotra et al, 2009). This data suggests that IFN may be a good therapeutic option for norovirus gastroenteritis.…”
Section: Other Strategies To Stop Norovirus Replicationmentioning
confidence: 88%